The impact of a project organisational culture and team rewarding on project performance - Aljaz Stare (Journal for East European Management Studies, 2012)
The purpose of this paper is to identify the level of project organisational culture in Slovenian enterprises and the impact of that culture on team motivation and project execution compared with monetary rewards for finalising projects in time and within budget. The research showed a high level of project organisational culture and that only one-third of enterprises have implemented reward systems, while the results of the analysis proved that a project organisational culture along with rewards increase the motivation of team members and consequently reduces project delays and cost overruns. – – Der Zweck dieses Artikels ist es, das Niveau der Projekt-Organisationskultur in slowenischen Unternehmen und die Auswirkungen dieser Kultur auf Team- Motivation und Projektabwicklung im Vergleich zu Geldprämien für pünktlich und budgetgerecht abgeschlossene Projekte zu identifizieren. Die Untersuchung zeigt eine hohe Stufe der Projekt-Organisationskultur und dass nur ein Drittel der Unternehmen Vergütungssysteme umgesetzt hat. Währenddessen zeigen die Analysenergebnisse, dass die Projekt-Organisationskultur zusammen mit Belohnungen die Motivation der Teammitglieder fördert und dadurch Projektverzögerungen und Kostenüberschreitungen reduziert.
Keywords: 650; project; organisation culture; reward; motivation